Comparison of mathematical models for description of desorption curves of sweet corn seeds - Araújo, Eduardo Fontes; Corrêa, Paulo César; Silva, Roberto Ferreira da (Pesquisa Agropecuaria Brasileira, 2001)
This work had the goal to determine the desorption curves of seeds of sweet corn cultivars Superdoce and Doce Cristal, and to adjust mathematical models to obtained data. Corn seeds were submitted to desorption under different temperature conditions (30, 40, 50 and 60oC), associated with different relative humidity (30, 40, 50 and 60%) until reaching the equilibrium humidity. The following models of regression analysis were adjusted to the experimental data: Henderson-Thompson, Chung-Pfost, Copace, Sigma-Copace, Sabbah and Smith. Seeds of both cultivars showed similar hygroscopic equilibrium. For both cultivars, the equations of Chung-Pfost, Sabbah and Smith, showed the best adjustments to the experimental data, with slight superiority of the first one.